Evaluating Productivity of Chinese Microfinance Institutions: A Malmquist Approach - Mia, Md Aslam; Zhang, Miao; Rasiah, Rajah; Alam, A.S.A. Ferdous (Taylor & Francis, 2018)
While the prime objective of Microfinance Institutions (MFIs) is to alleviate poverty, their sustainability is largely dependent on their productivity. Using the Malmquist approach and a panel dataset of 21 MFIs, this paper analyzes changes in the productivity of China’s MFIs between 2010 and 2012. Our findings reveal that the productivity of the MFIs in China stagnated due to the lack of technological change, despite progress in technical efficiency. Technical efficiency has been bolstered by improved management practices and size effect. The findings help improve our understanding of the Chinese microfinance sector in general, and MFIs’ productivity in particular. One policy implication that can be drawn from the evidence is to encourage MFIs participation in innovation activities, so that the stimulation of technological change can improve the overall productivity of Chinese MFIs.